2021
DOI: 10.3390/nano11112975
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Energy Harvesting Technology—From Self-Powered Sensors to Self-Sustained IoT, and New Applications

Abstract: With the fast development of energy harvesting technology, micro-nano or scale-up energy harvesters have been proposed to allow sensors or internet of things (IoT) applications with self-powered or self-sustained capabilities. Facilitation within smart homes, manipulators in industries and monitoring systems in natural settings are all moving toward intellectually adaptable and energy-saving advances by converting distributed energies across diverse situations. The updated developments of major applications po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 321 publications
(423 reference statements)
0
53
0
Order By: Relevance
“…In recent years kinetic energy harvesting from the human body and machinery-induced vibration motion is in extensive research aimed at providing sustainable power for portable wearable electronics, healthcare sensors, IoT's, and self-powered sensor networks. [1][2][3][4][5] In kinetic energy technology has been verified. [27][28][29] However, the triboelectric property of siloxene and polymer composites is not revealed yet.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent years kinetic energy harvesting from the human body and machinery-induced vibration motion is in extensive research aimed at providing sustainable power for portable wearable electronics, healthcare sensors, IoT's, and self-powered sensor networks. [1][2][3][4][5] In kinetic energy technology has been verified. [27][28][29] However, the triboelectric property of siloxene and polymer composites is not revealed yet.…”
Section: Introductionmentioning
confidence: 93%
“…In recent years kinetic energy harvesting from the human body and machinery‐induced vibration motion is in extensive research aimed at providing sustainable power for portable wearable electronics, healthcare sensors, IoT's, and self‐powered sensor networks. [ 1–5 ] In kinetic energy harvesting research various transduction principles are practically/theoretically verified and demonstrated such as electromagnetic, [ 6,7 ] piezoelectric, [ 8,9 ] and triboelectric [ 9–26,36,37,42,43,47–61 ] methods. Among these methods, triboelectric nanogenerators (TENG) based on the basic principle of contact electrification and electrostatic induction are contrived as the highly efficient sustainable power alternatives and effective platforms for self‐powered sensing owing to the high voltage feature (at low frequency), low cost, lightweight, wearability, and boundless material choices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by adopting an energy-harvesting solution, the energy of the system can be kept available to carry out the assigned tasks in real time and continuously, which remains challenging for different applications, such as in the case of real-time and continuous pulse monitoring [79], motion tracking [80], exoskeleton manipulation [81] and the maintenance and monitoring of implantable devices [82]. To this end, providing continuous and efficient power supply to wearable and implantable devices presents a highly addressed challenge in recent research [83][84][85]. As part of this, integrating energy-harvesting technologies with taskoffloading approaches allows end devices to endure for a long time to support long-term task processing [86][87][88].…”
Section: Energy Consumption Of Wireless Nodesmentioning
confidence: 99%
“…Therefore, several efforts have been made by the scientific community over the past decades by exploring sustainable, renewable, and green energy sources to fulfill the future demand of energy in an effective and environment-friendly way. Besides this, with the forthcoming Internet of things(IoT) and artificial intelligence era, the need for smart electronics with multiple functionalities, portable, flexible, and miniaturization concepts are highly desirable ( Liu et al., 2019 , 2021a , 2021b ). Till now, most of the energy requirements in the electronic devices are fulfilled by the batteries even though it endows several drawbacks due to their short life span, durability, short charging/discharging, heavyweight, rigid, bulky, and overheating nature ( Armand and Tarascon, 2008 ; Van Noorden, 2014 ).…”
Section: Introductionmentioning
confidence: 99%